Homologia semialgébrica sobre corpos reais fechados - Pereira, Rodrigo Mendes (2012)
This thesis is based on a series of papers published by H. Delfs and M. Knebusch on a homology theory to semialgebraic spaces on real closed fields. In this work, we collect the definitions and main results on the theory of semialgebraic homology. Furthermore, as application of this theory, we present a proof of the theorem of Ax-Grothendick for polynomials applications on real closed fields.